Record Center Sekolah Vokasi UGM: Analisis Kebutuhan, Rancangan, dan Desain untuk Teaching Industry - Indah Novita Sari (Program Studi Kearsipan, DBSMB SV UGM, 2017)
AbstractThe planning of the facilities to support archival technical activities has become a challenge for archivists in the 21st century. This benefits the efficiency of organizational needs and the overall protection of archives owned by an organization such as Vocational College, Universitas Gadjah Mada. This study is important since every organization needs an inactive records storage, but until now Vocational College has not had it yet. This study aims to determine the needs of Records Center in Vocational College and planning Record Center especially the space and equipment needed.The method used in this research is literature research method. Data collection techniques used literature study and participant observation. The literature source is used to obtain the data of planning procedure, while participant observation is used to obtain the primary data related to the need and the volume of the archive.Based on the results of needs analysis, it was found that Vocational College need a Record Center for inactive records storage, student learning facilities and meeting stakeholder needs. The steps to be considered are requirement analysis (calculation of archive volume, space requirement, facility requirement & infrastructure as well as location selection analysis) space planning and layout. The type of Record Center developed is the Offsite Record Center located in Kulon Progo. IntisariPerencanaan sarana prasana menjadi tantangan tersendiri bagi para arsiparis di abad 21. Hal ini memberikan keuntungan bagi efisiensi kebutuhan organisasi dan perlindungan menyeluruh bagi arsip yang dimiliki oleh Sekolah Vokasi, Universitas Gadjah Mada. Kajian ini menjadi penting mengingat setiap organisasi membutuhkan tempat penyimpanan arsip inaktif, namun sampai saat ini Sekolah Vokasi belum memilikinya. Penelitian ini bertujuan untuk mengetahui kebutuhan Record Center di Sekolah Vokasi dan melakukan perencanaan Record Center khususnya ruang dan peralatan yang dibutuhkan.Metode yang digunakan dalam penelitian ini adalah metode penelitian kepustakaan. Teknik pengumpulan data menggunakan studi pustakan dan observasi partisipan. Sumber pustaka digunakan untuk memperoleh data prosedur perencanaan, sedangkan observasi partisipan digunakan untuk memperoleh data primer terkait kebutuhan dan volume arsip.Berdasarkan hasil analisis kebutuhan, ditemukan bahwa Sekolah Vokasi memerlukan Record Center untuk tempat penyimpanan arsip inaktif, sarana pembelajaran mahasiswa dan memenuhi kebutuhan stakeholder. Langkah-langkah yang perlu diperhatikan adalah analisis kebutuhan (perhitungan volume arsip, kebutuhan ruang, kebutuhan sarana & prasarana serta analisis pemilihan lokasi), perencanaan ruang dan layout. Jenis Record Center yang dikembangkan adalah offsite Record Center yang berlokasi di Kulon Progo.